Modelling COVID 19 Epidemics: The Role of Social Distancing and Isolation - Patrick Noah, OKOLO; Abu, ONOJA (Covenant Journal of Physical and Life Sciences, 2021)
Coronavirus disease 2019 pandemic, popularly known as the COVID 19 pandemic, was one of the most dreaded pandemics in the history of human epidemiology. It negatively impacted the health and economy of the whole world, leading to a global economy shutdown. This study aims to develop a mathematical model for COVID 19 transmission to investigate the role of social distancing and isolation. Therefore, a mathematical model for COVID 19 incorporating social distancing and isolation of exposed and infectious individuals as controls were formulated. The basic reproduction number, as an epidemic threshold, was computed by the next-generation approach. The model has a globally asymptotically stable disease-free equilibrium whenever the basic reproduction number is less than unity. The numerical results show that whilst COVID 19 can spark a major epidemic in the absence of control. It can be contained with optimum enforcement of rules. The findings of this study reveal that an optimum combination of social distancing and isolation as a control strategy is the most effective and is therefore recommended.